Is Extreme Poverty Going to End? An Analytical Framework to Evaluate Progress in Ending Extreme Poverty - Yoshida, Nobuo; Uematsu, Hiroki; Sobrado, Carlos E. (World Bank, Washington, DC, 2014)
The World Bank has recently adopted a target of reducing the proportion of population living below US$1.25 a day at 2005 international prices to 3 percent by 2030. This paper reviews different projection methods and estimates the global poverty rate of 2030 modifying Ravallion (2013)'s approach in that it introduces country-specific economic and population growth rates and takes into account the effect of changes in within-country inequality. This paper then identifies key obstacles to meeting the target and proposes a simple intermediate growth target under which the global poverty rate can be reduced to 3 percent by 2030. The findings of the analysis lend support to Basu (2013)'s argument that accelerating growth is not enough and sharing prosperity within and across countries is essential to end extreme poverty in one generation.